The PPAT Responsibilities in Issuing APHT for Default Debtors at BKK Mayong Jepara - Agustina, Ita Sahara; Bawono, Bambang Tri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This research aims to identify and analyze the legal roles and responsibilities of the PPAT in issuing APHT for debtors who default on BKK Branc. Mayong Jepara. This research approach uses Juridical Sociolology, which is research through a statutory approach and examines laws that have problems in practice. The analytical knife in this paper uses the theory of legal certainty and the theory of responsibility. The results of this study indicate that the role of the Land Deed Making Officer (PPAT) in the process of imposing Mortgage Deeds at BKK Branc. Mayong Jepara, namely the Mortgage Granting Stage, Registration Process and Mortgage Issuance. PPAT's responsibilities are limited to making, registering, and issuing APHT. In the event of default, PPAT is only a bridge between debtors and creditors to find and solve problems. PPAT's legal responsibilities include criminal responsibility, civil responsibility, and administrative responsibility. However, in the event of a default committed by the debtor at Bank BKK Mayora Jepara Branch, it is no longer the responsibility of the PPAT. PPAT is only responsible for what he makes and does. Regarding products from PPAT that are used by clients to apply for credit which later defaults, PPAT no longer has legal responsibilityKeywords: Credit; Default; Responsibility.